A rainbow trout Oncorhynchus mykiss strain with higher aerobic scope in normoxia also has superior tolerance of hypoxia. Issue 2 (12th February 2018) - Zhang, Y.; Healy, T. M.; Vandersteen, W.; Schulte, P. M.; Farrell, A. P.
Abstract : This study compared parr from three strains of rainbow trout Oncorhynchus mykiss to examine intraspecific variation in metabolic traits, hypoxia tolerance and upper thermal tolerance in this species. At the strain level, variation in absolute aerobic scope (AAS), critical oxygen level (O2crit ), incipient lethal oxygen saturation (ILOS) and critical thermal maximum (CTmax ) generally exhibited consistent differences among the strains, suggesting the possibility of functional associations among these traits. This possibility was further supported at the individual level by a positive correlation between ILOS and O2crit and a negative correlation between O2crit and AAS. These results indicate that intraspecific differences in hypoxia tolerance among strains of O. mykiss may be primarily determined by differences in the ability to maintain oxygen uptake in hypoxia and that variation in aerobic scope in normoxia probably plays a role in determining the ability of these fish to sustain metabolism aerobically as water oxygen saturation is reduced.